2020
DOI: 10.3390/rel12010002
|View full text |Cite
|
Sign up to set email alerts
|

Using Intersectional Perspectives in the Studies of Non-Religion Ritualization

Abstract: In the 21st century, the Church of Sweden has lost its dominant position regarding the ritualization of births, marriages, and deaths in Sweden. Above all, name giving ceremonies, civil weddings, and civil funerals have become more common. The purpose of this article is to illustrate how intersectional perspectives can improve the understanding of the construction of non-religion in life-cycle ritualization, such as name giving ceremonies and civil funerals, performed beyond religious or non-religious organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In previous research, religion and secular ity have often been investigated as single categories standing apart from other social categories, leaving intersectional per spectives absent (Jarnkvist 2021;Reuter and Murray 2022). It is the same in studies of the construction, for example, of gender and class in Swedish, as well as international studies on rituals (see e.g.…”
Section: Intersectionalitymentioning
confidence: 99%
See 1 more Smart Citation
“…In previous research, religion and secular ity have often been investigated as single categories standing apart from other social categories, leaving intersectional per spectives absent (Jarnkvist 2021;Reuter and Murray 2022). It is the same in studies of the construction, for example, of gender and class in Swedish, as well as international studies on rituals (see e.g.…”
Section: Intersectionalitymentioning
confidence: 99%
“…The studies have shed light on ritualization as a complex process constructed in interaction with the social context in which it occurs. Studies have revealed, for example, that civil funerals may both relate to and express distance from religion in different ways and that place is essential for how this is done (Jarnkvist 2019(Jarnkvist , 2021. The theory is also relevant, for example, in studies on ritual change through history and analysing the influence of consumption and popular culture in ritualization.…”
Section: Ritual Practice Theorymentioning
confidence: 99%
“…Intersectionality relates to the complex experience of belonging to multiple identities and social groups [39,40]. Intersectionality has its roots in Black feminism [41] and demonstrates how overlapping axes of oppression relating to gender, sexual orientation, race, religion, national origin, and class have an effect on people who belong to more than one minority community [42][43][44]. According to Collins and Bilge [45], it is of great importance to not only see intersectionality regarding the effect that multiple identities have on one's self, but to explore the impact of multiple identities on power imbalances and inequalities.…”
Section: Intersectionality and Multiple Stigmatisationmentioning
confidence: 99%